Konstruksi Berita Online tentang Kecelakaan Pesawat Sriwijaya Air SJ-182 - Anggriani, Putri Geo; Wibawa, Darajat; Rusmulyadi, Rusmulyadi (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
Online media is a mass media that has high speed in spreading news, Suara.com and Okezone.com are the result of the online media. Applying Robert N. Entman's framing model to find out how Suara.com and Okezone.com package news from the perspective of highlighting issues from all aspects used in the news of the Sriwijaya Air SJ 182 plane crash. Using qualitative research methods and focusing more on logic and thinking logically. inductive. Overall, in this study, the highlighting issues on Suara.com and Okezone.com have similarities in conveying the chronology of the Sriwijaya Air plane crash. However, Okezone.com's neat, clear, and easy-to-understand news packaging makes it superior to Suara.com.